Equity research Symrise ag - solid and robust strategy - Ganswig, Jessica (2021)
This work project, Equity Research Symrise AG-A Solid and Robust Strategy, analyzes Symrise, one of the globally leading flavor and fragrance suppliers and its development in the aroma, flavor and fragrance market. The purpose of this report is to determine the company’s position in the industry and trends that drive growth to develop a valuation model in order to calculate the share price of Symrise as of 31stDecember 2021. The final recommendation to investors after conducting the analysis is to buy the stock.